A COMPARATIVE STUDY OF THE QUALITY OF MATHEMATICS LEARNING ASSESSMENT INSTRUMENTS BASED ON THE 2013 CURRICULUM AND THE MERDEKA CURRICULUM FROM THE PERSPECTIVE OF TEACHERS IN JUNIOR HIGH SCHOOLS IN WEST TONDANO DISTRICT - Mamangkey, Tegar F.R.; Maukar, Marvel G.; Ermita, Ermita (Universitas Tanjungpura, 2026)
The transition period between the 2013 Curriculum and the Independent Curriculum presents challenges for teachers in designing and implementing mathematics learning assessment instruments that align with curriculum requirements. The problem in this research stems from teachers' suboptimal understanding of how to develop assessment instruments for both curricula. This study aims to describe the quality of mathematics learning assessment instruments and examine their comparison based on teachers' experiences implementing the 2013 Curriculum and the Independent Curriculum in junior high schools in West Tondano District. This study used a qualitative phenomenological approach to understand teachers' subjective experiences in designing and using assessment instruments. Data were collected through in-depth interviews, observations, and documentation with mathematics teachers who have implemented both curricula. Data analysis was conducted through phenomenological reduction, grouping themes into meaningful themes, and extracting the essence of teachers' experiences related to assessment practices. Data validity was maintained through triangulation and member checking. The results showed that teachers perceived the assessment instruments in both curricula as accommodating aspects of knowledge, attitudes, and skills and utilizing diagnostic, formative, and summative assessments on an ongoing basis. However, teachers' experiences indicated that the Independent Curriculum provided more flexibility in developing contextual assessments and using technology, while the 2013 Curriculum was more structured in its assessment procedures. These findings confirm that assessment quality is not solely determined by the curriculum, but by how teachers interpret and implement assessment in their learning practices.